Discriminatory Image Caption Generation Based on Recurrent Neural Networks and Ranking Objective - Geetika,; Jain, Tulsi (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes a novel approach for image caption generation. Being able to describe the content of an image in natural language sentences is a challenging task, but it could have great impact because great amount of resources is required to meet the demands of vast availability of image dataset. The growing importance of image captioning is commensurate with requirement of image based searching, image understanding for visual impaired person etc. In this paper, we develop a model based on deep recurrent neural network that generates brief statement to describe the given image. Our models use a convolutional neural network (CNN) to extract features from an image. We used ranking objective to pay attention to subtle difference between the similar images to generate discriminatory captions. MS COCO dataset is used, nearly half of the dataset for training and one fourth of dataset for each validation and testing. For every image five captions are provided to train the model Our model consistently outperforms other models with on ranking objective. We evaluated our model based on BLEU, METEOR and CIDEr scores.